Renal function, complications, and outcomes of a reduction in tumor size after transarterial embolization for renal angiomyolipomas: a meta-analysis. Issue 4 (April 2019) - Lin, Letao; Li, Xinfei; Guan, Haitao; Wang, Jian; Tong, Xiaoqiang; Yang, Min; Zou, Yinghua
Objective: The present study aimed to evaluate renal function, complications, and changes in tumor size after transarterial embolization for patients with renal angiomyolipomas. Methods: We performed a meta-analysis of transarterial embolization in patients with renal angiomyolipomas from January 1994 to April 2018. Endpoints of interest were the estimated glomerular filtration rate, serum creatinine levels, blood urea nitrogen levels, complications, and reduction of tumors. Results: A total of 30 studies comprising 653 patients were included. A total of 32.0% of patients were treated by urgent transarterial embolization for spontaneous ruptured renal angiomyolipomas. Other patients sought to relieve symptoms or received embolism prophylactically. The estimated glomerular filtration rate showed no significant difference between before and after embolization. In 363 patients with data on complications, post-embolization syndrome occurred most frequently (54.0%). Only 16 (4.4%) patients had major complications. The diameter of sporadic angiomyolipomas was reduced by a mean of 2.09 cm (95% confidence interval [CI], 0.73–3.45 cm; I 2  = 29.3%) and they were reduced in size by 30.0% (95% CI, 16.0%–44.0%; I 2  = 27.9%). Conclusions: Transarterial embolization of renal angiomyolipomas affects renal function preservation, with a low complication rate. Transarterial embolization is useful for sporadic and tuberous sclerosis complex-related angiomyolipomas.